Ketelitian Model Kinematik untuk Memprediksi Karakteristik Longsor (Studi Kasus : Zona Longsor di Ciloto-Puncak, Jawa Barat) - Sadarviana, Vera; Z. Abidin, Hasanuddin; Kahar, Joenil; Santoso, Djoko; K, Wedyanto (Indonesian Journal of Geospatial, 2012)
Abstract. The geodetic approach based on extraterrestrial survey measurements can be used to study phenomenon, especially to monitoring of material movement characteristic. Landslide is one of prominent catastrophe that continuously affecting in Indonesia, especially in rainy season. In mountainous terrain and areas of steep slope of Indonesia, landslides are frequent, especially where land cover has been removed. Landslides destroy not only environment and property, but usually also cause deaths. Landslide mitigation is therefore very crucial and should be done properly. The velocity and acceleration of several monitored point covering the landslide zone area can be estimated using the geodetic approach. Knowing the relation among these three variables in spatial and temporal domain will be useful for identifying the characteristics of landslide. This information can then be used for better strategy of landslide hazard mitigation. Accuracy of the use of kinematic models for prediction of avalanche characteristics need to be validated so that mitigation will be done correctly. Validation is done by doing a comparison between model predictions and the size of the data and statistical tests for the feasibility of prediction of each point of the GPS monitor. Validation is known that the predicted results at some GPS monitor point is not suitable for use. With the vector of the movement of materials, we know the direction and scalar, velocity and acceleration of material displacement. The movement of landslide materials at Ciloto Zone dominated north-west to south-easterly direction and speed to slow very slow (creep).Â Keywords: accuracy, characteristics, kinematic model, landslide.